PENGARUH MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMK MUHAMMADIYAH 1 PADANG - Sy, Fika Marta Sari; Emidar, Emidar; Arief, Ermawati (Universitas Negeri Padang, 2018)
This research aims to describe the influence model of discovery learning the skills of writing text exposition class X SMK Muhammadiyah 1 Padang. The type of this research is quantitative research done using experimental design. The results of this research are three: (1) writing text skills exposition before using discovery learning model of class X SMK Muhammadiyah 1 Padang are in qualifying Nearly Enough (HC) with an average value of 66,62, (2) writing text skills exposition after using discovery learning model of class X SMK Muhammadiyah 1 Padang are in qualification More than Enough (HC) with an average value of 78,83, and (3) exposition writing text skills class X SMK Muhammadiyah 1 Padang after using the model of discovery learning better than before using the model of discovery learning.Â Kata Kunci: pengaruh, model discovery, teks eksposisi